Noninvasive ventilation in critically ill patients with the Middle East respiratory syndrome - Alraddadi, B; Qushmaq, I; Al-Hameed, F; Mandourah, Y; Almekhlafi, G; Jose, J; Al-Omari, A; Kharaba, A; Almotairi, A; Al Khatib, K; Shalhoub, S; Abdulmomen, A; et al. (Wiley, 2019)
Background: Noninvasive ventilation (NIV) has been used in patients with the Middle East respiratory syndrome (MERS) with acute hypoxemic respiratory failure, but the effectiveness of this approach has not been studied. Methods: Patients with MERS from 14 Saudi Arabian centers were included in this analysis. Patients who were initially managed with NIV were compared to patients who were managed only with invasive mechanical ventilation (invasive MV). Results: Of 302 MERS critically ill patients, NIV was used initially in 105 (35%) patients, whereas 197 (65%) patients were only managed with invasive MV. Patients who were managed with NIV initially had lower baseline SOFA score and less extensive infiltrates on chest radiograph compared with patients managed with invasive MV. The vast majority (92.4%) of patients who were managed initially with NIV required intubation and invasive mechanical ventilation, and were more likely to require inhaled nitric oxide compared to those who were managed initially with invasive MV. ICU and hospital length of stay were similar between NIV patients and invasive MV patients. The use of NIV was not independently associated with 90‐day mortality (propensity score‐adjusted odds ratio 0.61, 95% CI [0.23, 1.60] P = 0.27). Conclusions: In patients with MERS and acute hypoxemic respiratory failure, NIV failure was very high. The use of NIV was not associated with improved outcomes.